BEHAVIOURS OF STUDENTS OF PRIMARY SCHOOL AS REGARDS OUTSIDE OF SCHOOL SAFETY IN RELATION WITH DEMOGRAPHICS CHARACTERISTICS - ANGELIKI, Mavropoulou; HATZIMANOUIL, Dimitris; KANIOGLOU, Angelos (Studia Universitatis Babeş-Bolyai Educatio Artis Gymnasticae, 2016)
Introduction. The outside of school safety is an important factor of insurance of student’s health in primary school. Objective: The purpose of the study was to present, to compare and to estimate the behaviours of child’s of fifth and sixth class of elementary schools in regards the outside of school safety in relation with the demographics characteristics. Method: In the research was used the division of adolescent and school health (DASH) questionnaire from CDC (Centres for Disease Control and Prevention) that was given to 247 school students of Thessaloniki, Ioannina and Edessa anonymously and voluntary. Specifically, there were questions in the questionnaire on personal characteristics, demographic data and questions about outside of school safety. Results: From the total students 96% answered the questionnaire. The results showed that students who live in city with more population showed bigger safety as regards the use of helmet when they bicycle. Girls in comparison to boys have more awareness as regards the use of helmet. Age is conversely analogical with the use of helmet. The school achievement is analogical with the use of helmet and the use of the belt in the car. Parents’ educational level also plays an important role for the use of helmet when bicycle and for the use of the belt and safety to the transportation by car. Conclusions: In conclusion, the demographic characteristics play an important role for the children of this age for the configuration of the behaviours as regards the outside of school safety.